Pendidikan Karakter dalam Buku Puisi Hyang Karya Abdul Wachid B.S. (Analisis Profetisme Kuntowijoyo) - Faiz Adittian (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2018)
AbstractProphetic literature is a literary work based on prophetic characteristics. The pillars of prophetic literature are divided into the transcendence dimensions, the liberation dimensions, and the humanism dimensions. As in this research, in Hyang poetry book by Abdul Wachid B.S. contain with a strong prophetic value in divine and social values. Of course, each poem that written is the actualization of life that reflect the poet's personalities. From this prophetic poetry, will be searched the value of character education that contained in the literary works (poetry). So with poetry, the reader will find the value of character education in poetry that presented by the poet in his poetry. Keywords: Prophetic Literature, Hyang Poetry Book, The Value Of Character Education AbstrakSastra profetik merupakan karya sastra yang berlandaskan atas sifat-sifat kenabian. Pilar sastra profetik terbagi ke dalam dimensi transendensi, dimensi liberasi, dan dimensi humanisme. Seperti dalam penelitian ini, di dalam buku puisi Hyang karya Abdul Wachid B.S. banyak mengandung nilai profetik yang kental akan nilai-nilai ketuhanan dan sosial. Tentunya, setiap puisi yang dituliskan merupakan aktualisasi dari kehidupan yang mencerminkan kepribadian penyair itu sendiri. Berangkat dari puisi profetik ini, akan dicari nilai pendidikan karakter yang terkandung di dalam karya sastra (puisi). Sehingga melalui puisi, pembaca akan menemukan nilai pendidikan karakter di dalam puisi yang disuguhkan oleh penyair di dalam puisinya. Kata Kunci: Sastra Profetik, Buku Puisi Hyang, Nilai Pendidikan Karakter.